The Application of Cruscal Algorithm in Determining the Shortest Routes Tourism in Medan - Rismunanda Rismunanda; Normalina Napitupulu (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2022)
With technological advances today, the application of science in mathematics is becoming increasingly broad, including determining the optimal path on a path using a graph. As we know, the city of Medan and its surroundings is one of the tourist destinations in Indonesia, which has many interesting places to visit. Tourists inside and outside have even planned to visit various tourism centers in the city of Medan. With so many tourist objects to be visited, a graph will be very helpful in determining the paths that have the shortest path, the path that produces the least cost, and the path that is the most optimal. Kruskal's algorithm is an algorithm in graph theory that looks for the minimum spanning tree for a weighted and connected graph. Kruskal's algorithm is one of the algorithms for determining the shortest route from one tourist attraction to another.